COMPARISON OF CHEMICAL CASTRATION SANCTIONS AGAINST PERPETRATORS OF CHILD SEXUAL VIOLENCE IN IN-DONESIA AND SOUTH KOREA - Pratama, Yudi; Irzal Fardiansyah, Ahmad; Nikmah Rosidah; Maya Shafira; Gunawan Jatmiko; Rini Fathonah (Sriwijaya Crimen and Legal Studies, 2025)
Chemical castration punishment is regulated in Law No. 17 of 2016 about Child Protection, which provides additional sanctions for perpetrators of child sexual crimes. In South Korea, it is regulated in the South Korean Bill on Prevention and Handling Perpetrator Violence Sexual to However, the implementation of this law has encountered various obstacles, including unclear implementation procedures and rejection from several medical circles. Even though there are aiming to protect children from sexual violence, criticism has emerged regarding potential human rights violations. tendency to repeat crimes. With a more structured system, South Korea has succeeded in reducing the recidivism rate through a rehabilitation approach and long-term supervision. This study uses a normative legal approach using a legislative approach, a conceptual approach and a comparative legal approach. The results of the study show that although both countries have the same goal of protecting children from sexual violence, there are significant differences in the implementation and effectiveness of chemical castration sanctions in Indonesia which carries out execution aimed at the profession doctor while South Korea was handed over to court as execution castration chemical. This study aims to provide insight into the comparison of legal policies in the two countries and their implications for the protection of child sexual violence victims. Meanwhile, South Korea became the first country in Asia to implement chemical castration in 2011. This policy was implemented based on the results of a medical diagnosis indicating that the perpetrator had.